Pharmacognostic studies of Pavonia senegalensis (cav.) Liestner (malvaceae) leaf - Shehu, Umar Faruk; Abubakar, Abdulmumin Zayd; Ibrahim, Garba (Journal of Current Biomedical Research, 2023)
Pavonia senegalensis (Cav.) Liestner (Malvaceae) is a plant used in African Traditional medicine. The aim of this study was to carry out pharmacognostic studies and HPLC fingerprinting on the leaves of P. senegalensis for standardization purposes. Macroscopic, organoleptic, microscopic and physico-chemical evaluation were carried out on the leaf of the plant. The diagnostic microscopic features of the leaf include anomocytic stomata, unicellular covering stellate trichomes, polygonal epidermal cells with beaded anticlinal walls. The powdered leaves under light microscope showed the presence of numerous unicellular covering trichomes and clusters of rosette calcium oxalate crystals with groups of epidermal and parenchyma cells. The physico-chemical characteristics determined are total ash 10.53 %, acid-insoluble ash 4.83 %, moisture content 7.26 %, water-soluble and alcohol soluble-extractive 15.15 and 12.25 % respectively. The presence of heavy metals determined in the leaves of P. senegalensis were zinc and lead which were 0.24 and 4.00 mgkg-1 respectively while cadmium, arsenic and mercury were not detected. The phytochemical screening of the aqueous ethanol leaf extract of P. senegalensis showed the presence of phenolic compounds (flavonoids and tannins) and steroids/triterpenes (saponins). The HPLC fingerprints of the aqueous ethanol leaf extract determined under optimized conditions showed 5 peaks with retention times 1.26, 1.56, 2.18, 3.10 and 4.34 mins. The result of this study can be used to evaluate any sample or products labelled as Pavonia senegalensis.